Status of cattle and buffalo insurance scheme in Uttar Pradesh: A case of Gorakhpur district - Khan, Mohd Ameer (Indian Journal of Dairy Science, 2017)
Since 1971 the Indian Government has catalyzed the livestock insurance market through the Small Farmers’ Development Agency, which has introduced various schemes for livestock-rearing farmers by providing funding for the purchase of livestock through loans and a premium subsidy for the insurance cover. The livestock insurance has not operated in a significant way till date and still evolving in terms of scope, spread and structure. With this theoretical background, the present study has focused on the situation of livestock insurance in present scenario and proposed some policy implication for insurance in livestock sector. This study included 120 cattle and buffalo owners who insured there dairy animals in different insurance schemes operated in Gorakhpur district of Uttar Pradesh. The primary data was collected by both qualitative and quantitative method using interview schedule, questionnaire, focus group discussion and observation method. The study revealed that most of the dairy animal owners had buffalo as a main dairy animal in their herd. All the indigenous cows were insured through government schemes whereas, crossbred animals were insured under NLIS. More than two third of the policies for crossbred cows and buffaloes were long term. Crossbred cows were insured more than other milch animals because farmers perceived that more risk associated with these animals. More than 50% claims were reported in case of crossbred cows and buffaloes insured under government schemes. Public insurers frequently experienced high claim ratio due to frauds by the insurers. The livestock insurance scheme should be revised from the current practices and make it more farmer friendly.